Parathyroid hormone related protein in hypercalcaemia of Hodgkin's disease. Issue 6 (June 1992) - Bolo-Deoku, J; Basu, S; Lakhani, S; Dunne, F; Ratcliffe, W A; Clarke, M; Barron, J L
Abstract : The role of parathyroid hormone related protein (PTHRP) as a humoral mediator of hypercalcaemia was investigated in a patient with lymphocyte depleted Hodgkin's disease during an episode of hypercalcaemia, using an immunohistochemical staining technique for PTHRP on the tumour tissue and an immunoradiometric (IRMA) assay for PTHRP1-86 on the patient's plasma. The plasma PTHRP was less than 0.23 pmol/l in the range found in normocalcaemic controls, and the immunohistochemical staining was not positive for protein. PTHRP did not have a role in the pathogenesis of hypercalcaemia in this patient.